IVT-SAPAS: Low-Input and Rapid Method for Sequencing Alternative Polyadenylation Sites. - Yonggui Fu; Yutong Ge; Yu Sun; Jiahui Liang; Liang Wan; Xiaojian Wu; Anlong Xu (PLoS ONE)
Gene transcribing with alternative polyadenylation (APA) sites leads to mRNA isoforms, which may encode different proteins or harbor different 3'UTRs. APA plays an important role in regulating gene expression network among various physiological processes, such as development, immune responses and cancer. Several methods of library construction for APA study have been developed to apply high-throughput sequencing. However, the requirement of high-input RNA and time-consuming nature of the current methods limited the studies of APA for the samples difficult to obtain. Here, we describe a new method based on our SAPAS in combining in vitro transcription (IVT) and magnetic beads purification. The new IVT-SAPAS provides a rapid and high-parallel procedure for APA library construction with low-input sample, which may be a new robust approach for studying APA.